IPad‐assisted reading fluency instruction for fourth graders with reading difficulties: A single case experimental design. (15th October 2020) - Mize, Min; Park, Yujeong
Abstract: The purpose of this study was to investigate the effect of iPad‐assisted reading instruction for fourth‐grade students' oral reading fluency and their attitudes towards reading. Three fourth‐grade students at‐risk for reading disabilities participated in an iPad‐assisted repeated reading programme that integrated repeated reading, vocabulary instruction, error correction and feedback procedures. During each intervention session, the participants practiced reading a fourth grade‐level text, engaged in repeated reading with the intervention agent and repeatedly read the text three or four times with error correction. The oral reading rate for the fourth‐grade text that they practiced and a transfer text (i.e., new text that students have not practiced before) served as the primary dependent variables. Their attitudes towards reading were measured before and after the intervention. Using a multiple baseline across participants design, we showed that the iPad‐assisted repeated reading programme improved all participants' oral reading rates on both the grade‐level text and the transfer text. Implications of the study and future directions were discussed. Lay Description: What is already known about this topic: Reading fluency is a critical component of effective reading instruction and an essential skill to become a skilled reader. iPad applications and their instructional features provide students with instructional opportunities that support a broad range of learning experiences. Tablet technology has been suggested as an effective tool for struggling readers, but less has been know about using iPad to teach reading fluency skills to students with reading difficulties. What this paper adds: Using two applications (a dictionary application for unknown words and a self‐management application for engagement and motivation) in iPad‐assisted instruction resulted in increases in oral reading fluency. iPad‐assisted reading fluency instruction contributed to the increasing trend and maintenance increase on both practiced text (during intervention) and unpracticed/new text. Students' oral reading fluency score was higher when students read the familiar text on iPad which they had already practiced during the intervention. Implications for practice and/or policy: The use of mobile technology can be a motivating component for struggling readers when it combines with explicit instruction that can support students to read a text with fluency. It is the responsibility of teachers and educators to find good applications by considering the strengths and needs of their struggling readers.